MODEL STUDENT LEARNING AND ESQ STKIP PANCA SAKTI BEKASI FACING INDUSTRIAL REVOLUSTION 4.0 - Dewi Endah Fajariana (Department of English Education, Universitas Panca Sakti Bekasi, 2019)
The flow of globalization has no longer stopped entering Indonesian territory accompanied by increasingly sophisticated technological developments, the world is now entering the industrial revolution era 4.0. Facing these challenges, universities are required to change, including in producing quality bachelor candidates for future generations. The target of these changes is students in universities, because future job competency needs are cognitive abilities, physical abilities, content skills, process skills, social skills, system skills, complicated problem solving skills, resource management skills and technical skills. Therefore, an innovative lecture is needed so that students do not feel bored and are able to master the science and technology received at college with stable emotional intelligence. Innovative lectures are the delivery of lecture materials using learning models so that students are not bored because the majority of STKIP students, especially economic education, work. This type of research uses a qualitative descriptive approach. Research that intends to understand the phenomenon of what is experienced by research subjects students who contract subjects of microeconomic theory, the Indonesian economy and the introduction of economics A and B.